THE INFLUENCE OF COMMUNICATION PATTERNS ON THE PERFORMANCE OF THE MAJU BERSAMA FARMER GROUP IN MANUSAK VILLAGE, KUPANG REGENCY - Novilma Maryeci Duka; Selfius P.N. Nainiti; Abraham R. Illu (Undana Press, 2026)
This study aimed to analyze the communication patterns applied in the Maju Bersama Farmer Group and to identify the factors within communication patterns that influence farmer group performance. The research was conducted in September 2025 using a survey method involving 22 members of the Maju Bersama Farmer Group. Data were collected through interviews using questionnaires, while secondary data were obtained from the Manusak Village Office. The sampling technique used was saturated sampling. The data were analyzed using descriptive analysis and multiple linear regression analysis. The results show that the communication pattern implemented in the Maju Bersama Farmer Group takes place through two-way communication, regular meetings, and informal communication. The group uses both Indonesian and local languages. Overall, communication runs fairly well, although it still needs to be improved to become more optimal. The regression analysis shows that communication patterns simultaneously have a significant effect on farmer group performance, with a contribution of 69.39%. Partially, communication frequency has a positive and significant effect, communication channels have a positive but insignificant effect, and communication effectiveness is the most dominant factor with a significant influence on farmer group performance in Naibonat Subdistrict.